The impact of parental absence on the mental health of middle school students in rural areas of Western China - Ren, Xiaohong; Lin, Cen; Pan, Lu; Fan, Qiuyue; Wu, Dapeng; He, JinLong; He, Ping; Luo, Jiaming (Frontiers in Public Health, 2025)
BackgroundExtensive research has established the association between parental absence and adolescent psychological well-being, particularly in the Chinese context. However, studies specifically examining the dual impact of parental separation and migration on psychological outcomes among adolescents in Western China remain relatively limited.AimThis study aims to systematically examine the association between various parental absence situations and mental health outcomes in early adolescence, with the objective of informing targeted interventions and policy formulations to optimize psychosocial support systems for vulnerable youth population.MethodsThe Wilcoxon rank-sum test was employed to analyze continuous and ordinal variables that exhibited non-normal distributions. To investigate the associations between various patterns of parental absence and psychological outcomes (depression, anxiety, and stress) among middle school students, binary logistic regression analysis was performed, while the model’s goodness-of-fit was evaluated by using the Hosmer-Lemeshow test, with a p > 0.05 indicating satisfactory model fit.ResultsThis cross-sectional study investigated mental health outcomes among a cohort of 8,606 middle school students, revealing notable prevalence rates of depressive symptoms (6.7%), anxiety (6.1%), and stress-related symptoms (8.1%). Multivariate analysis demonstrated that different forms of parental absence exerted substantial effects on mental health severity, with statistically significant associations for depression, anxiety, and stress (all p < 0.001). The results revealed that various forms of parental absence had a significant impact on depression, anxiety, and stress. Specifically, the combined impact of divorce and left-behind children (DLC) creates a synergistic effect, resulting in psychological risks (OR = 1.623–1.725, all p < 0.001), that are significantly higher than those associated with either factor individually (LBC/DC). Further analysis identified additional risk factors, including senior high school (OR = 1.486, p < 0.001), boarding school (OR = 1.155, p = 0.037), and girls (anxiety OR = 1.213, p < 0.001), all showing significant associations with adverse mental health outcomes.ConclusionOur study underscores significant mental health risks associated with diverse patterns of parental absence among adolescents in the Sichuan region. By fostering stronger parent–child bonds and providing targeted emotional support, it may be possible to mitigate the adverse psychological effects of parental absence and help adolescents better navigate these mental health challenges.